2014
DOI: 10.5194/bg-11-4123-2014
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen and dissolved organic carbon (DOC) losses from an artificially drained grassland on organic soils

Abstract: Abstract. -N) as well as dissolved organic carbon (DOC) and nitrogen (DON) concentrations and losses were studied for three and two years, respectively, in a small catchment dominated by a degraded peatland used as intensive grassland. Concentrations in the shallow groundwater were spatially and temporally very variable, with NO 3 -N being the most dynamic component . Ditch DOC concentration were lower than the groundwater DOC concentration of 50.6 ± 15.2 mg L −1 (14.9 to 88.5 mg L −1 ). Both DOC and N concen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…yr -1 S F B F ) are close to fluxes reported from some temperate 20 and boreal fens in Scandinavia and Canada (5 g C m -2 yr -1 , Strack et al, 2008;3.7 g C m -2 yr -1 , Juutinen et al, 2013) and German drained peat grasslands (5.2 g C m -2 yr -1 , Tiemeyer and Kahle, 2014), and are low compared to values from UK raised bogs (25 g C m -2 yr -1 , Dinsmore et al, 2010) and blanket bogs (33 g C m -2 yr -1 , Worrall et al, 2003). Other semi-natural and agricultural fens in the same region (East Anglia, UK), measured concurrently with our study, also had low DOC fluxes (4.1 7.9 g C m -2 yr -1 ), whilst semi-natural fens and peat grasslands in wetter parts of the UK had higher fluxes (Somerset; 10-22 g C m -2 yr -1 , Anglesey; 18-31 g C m -2 yr -1 ) (Evans et al, 2016a).…”
Section: Water Chemistry and Fluvial Carbon Lossessupporting
confidence: 84%
“…yr -1 S F B F ) are close to fluxes reported from some temperate 20 and boreal fens in Scandinavia and Canada (5 g C m -2 yr -1 , Strack et al, 2008;3.7 g C m -2 yr -1 , Juutinen et al, 2013) and German drained peat grasslands (5.2 g C m -2 yr -1 , Tiemeyer and Kahle, 2014), and are low compared to values from UK raised bogs (25 g C m -2 yr -1 , Dinsmore et al, 2010) and blanket bogs (33 g C m -2 yr -1 , Worrall et al, 2003). Other semi-natural and agricultural fens in the same region (East Anglia, UK), measured concurrently with our study, also had low DOC fluxes (4.1 7.9 g C m -2 yr -1 ), whilst semi-natural fens and peat grasslands in wetter parts of the UK had higher fluxes (Somerset; 10-22 g C m -2 yr -1 , Anglesey; 18-31 g C m -2 yr -1 ) (Evans et al, 2016a).…”
Section: Water Chemistry and Fluvial Carbon Lossessupporting
confidence: 84%
“…This study, amongst others, has revealed significant differences in the relationship between DOC : nitrate and discharge dependent on both geology and seasonal effects (Tiemeyer and Kahle, 2014;Thomas et al, 2016). The Chalk site exhibited little variation in DOC : nitrate with discharge due to the dominance of groundwater contribution at both high and low flows.…”
Section: Ecological Significance Of Temporal Variations In Doc : Nitrmentioning
confidence: 58%
“…Peatlands subjected to drainage (such as agricultural peats) leach more DOC than undisturbed ones (Frank et al, 2014). Nevertheless, studies on peatland restoration present mixed results of rewetting on the concentration of DOC (Tiemeyer and Kahle, 2014;Frank et al, 2014;Preston et al, 2011;Schwalm and Zeitz, 2015).…”
Section: Dissolved Organic Carbonmentioning
confidence: 99%